Aspectos rítmicos no minimalismo: elaboração de exercícios a partir do procedimento de defasagem e processos aditivos - Cunha, Katiane Cristine Faria da (2015)
This research aims the elaboration of rhythmic exercises based on rythmic aspects analyzed from minimalist composers. We start from the hypothesis that musical learning in most Brazilian universities does not prioritize contemporary music studies. It is not, therefore, a conceptual hypothesis, but a hypothesis that shows the importance of investing in that subject, that has taken us to get a glimpse of pragmatic questions (Boaventura, 2008) that mold the teaching and conceptual questions that may enrich the learning of the rhythmic aspect from a embodied mind (Fridman, 2013). Therefore, the research had as its general goal: the elaboration of exercises based on rhythmic structures utilized in Minimalism, highlighting the Phase Shifting processes and additive processes such as the Block Additive Process, and the Linear Additive Process, and as objective goals: to make a reflexion upon rhythm definition highlighting some approaches about this musical element throughout the musical history of the Ocidental Europe; to search for enlightenment on the minimalist movement (pre-classical phase) pointing out the intentions, influences and purposes of the compositions; to describe/analyze the processes utilized by Steve Reich (1936-) and Phillip Glass (1937-) in the previously mentioned phase; to elaborate rhythmic exercises based on those processes; to experience the elaborated exercises in Music Perception classes in the Music course at UFU. In order to reach these goals the methodology was based on the following steps: bibliographic review about the definition of rhythm; studies about rhythmic processes created in the twentieth century, especially in the minimalistic repertoire; elaboration of musical exercises (studies) involving Phase Shifting, Linear Additive Process and Black Additive Process; application of the exercises created on music grad-students at UFU; and, study of the results achieved with the application of the exercises. In the final considerations we highlight the need for elaborating musical practices befitting from paradigmatic emergent principles, the transference of a holistic vision to musical learning, considering that those legacies showed themselves as challenging to musical-educators nowadays